Plan de Negocio de Productos Turísticos de La Finca Cafetalera El Zapote, Cantón Chaguarpamba, Provincia de Loja - Castillo Castillo, Mayra Esther (2017)
The present research work had as objectives to propose a diagnosis for the farm; To design a proposal of the tourist products that will be offered in the same; And, socialize the business plan to those involved when presenting the proposal, acquiring suggestions that facilitated an efficient culmination. To do this we used the analytical, scientific, inductive, deductive and synthetic methods that facilitated the information obtained from the application of interviews and surveys. The results showed that the proposed business plan is feasible; Taking into account that an investment of $ 85,755.47 is required, projecting revenues of $ 35438.56 with a net present value of $ 38,901.74, internal rate of return of 11.85% and a cost benefit ratio of 1.99. Therefore, it is noteworthy to conclude that the implementation of the project on the farm contributes to its profitable increase, recommending that it be applied immediately as a way to boost tourism and contribute to the welfare of the community in general